Clinical pharmacogenomics: patient perspectives of pharmacogenomic testing and the incidence of actionable test results in a chronic disease cohort. (September 2017) - Mukherjee, Chandrama; Sweet, Kevin M; Luzum, Jasmine A; Abdel-Rasoul, Mahmoud; Christman, Michael F; Kitzmiller, Joseph P
Aim: This study aimed to examine pharmacogenomic test results and patient perspectives at an academic cardiovascular medicine clinic.Patients & methods: Test results for three common cardiovascular drug–gene tests (warfarin- CYP2C9-VKORC1, clopidogrel- CYP2C19 and simvastatin- SLCO1B1 ) of 208 patients in the Ohio State University-Coriell Personalized Medicine Collaborative were examined to determine the incidence of potentially actionable test results. A post-hoc, anonymous, patient survey was also conducted.Results: Potentially actionable test results for at least one of the three drug–gene tests were determined in 170 (82%) patients. Survey responses (n = 134) suggested that patients generally considered their test results to be important (median of 7.5 on a 10-point scale of importance) and were interested (median of 7.3 on a 10-point scale of interest) in a Clinical Pharmacogenomic Service.Conclusion: Attitudes toward pharmacogenomic testing were generally favorable, and potentially actionable test results were not uncommon in this cardiovascular medicine cohort.